Alexandronectes zealandiensis gen. et sp. nov., a new aristonectine plesiosaur from the lower Maastrichtian of New Zealand. Issue 2 (3rd March 2016) - Otero, Rodrigo A.; O'Gorman, José P.; Hiller, Norton; O'Keefe, F. Robin; Fordyce, R. Ewan
ABSTRACT: A fragmentary plesiosaur skull from lower Maastrichtian levels of the Conway Formation, New Zealand, is redescribed. Originally regarded as pertaining to two separate individuals, we argue that they represent a single individual belonging to a new aristonectine elasmosaurid, Alexandronectes zealandiensis gen. et sp. nov. This new taxon has common morphologies with other aristonectines such as expansion of the pterygoids extending posteriorly beyond the occipital condyle (as observed in Ar. quiriquinensis and probably in Kaiwhekea katiki ) and the presence of an 'A'-shaped squamosal arch in dorsal view. Otherwise, it is distinguished from these latter species by having different paraoccipital processes, a different mandibular glenoid, and an adult skull comparatively smaller than K. katiki and Aristonectes spp. The new taxon is a morphologically intermediate form between the dorsoventrally high skull of K. katiki and the mediolaterally expanded skulls of Aristonectes spp. The studied specimen is the second genus and species and the third report of an aristonectine recovered from lower Maastrichtian beds of New Zealand, emphasizing the diversity of this group in New Zealand and also indicating that aristonectines could include smaller species than those already known. http://zoobank.org/urn:lsid:zoobank.org:pub:5167B8FB-82F7-4F33-8663-EBF16692A9A0 SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Otero, R. A., J. P. O'Gorman, N. Hiller, F. R. O'Keefe, and R. E. Fordyce. 2016. Alexandronectes zealandiensis gen. et sp. nov., a new aristonectine plesiosaur from the lower Maastrichtian of New Zealand. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2015.1054494.